Retrospective Outcome Analyses for Headaches in a Pain Rehabilitation Interdisciplinary Program. Issue 3 (3rd September 2013) - Zheng, Yuxi; Tepper, Stewart J.; Covington, Edward C.; Mathews, Manu; Scheman, Judith
<x xml:space="preserve">Abstract</x> Background Incapacitating chronic migraine and other severe headaches can have significant impact on peoples' lives, including family and occupational functioning. Although a number of reports have investigated the prevalence and medical treatment of chronic headache, few have reported on the efficacy of treating these disorders within a comprehensive, intensive chronic pain rehabilitation program (CPRP), instead of a headache‐specific program. CPRPs provide treatment of headache by focusing not only on physical pain, but also its association with impaired mood and function. Methods We examined the efficacy of CPRP in patients with chronic headache via a retrospective analysis of 123 patients (76.4% female), ages 21 to 85, who completed the CPRP at the Cleveland Clinic between January 2007 and December 2011, and were diagnosed using International Classification of Headache Disorders, 2nd edition and International Classification of Headache Disorders, 2nd edition revision, with migraine or headache as a major complaint. Outcome measures included: pain intensity scores present at the moment of questioning where 10 is the maximal (0‐10/10), Depression Anxiety Stress Scale (DASS) scores, (measuring mood), and Pain Disability Index scores (measuring function). Repeated measures t‐tests were used. Results Average pain score on admission was 6.4, and 3.4 upon discharge. Average function on admission was moderately impaired, and normalized on discharge. The average depression score was in the moderate range, and had normalized on discharge. The average anxiety score on admission was in the severe range and was in the mild range on discharge. Conclusions Results indicate that individuals had statistically and clinically meaningful improvement in pain, mood, and function. Data suggest that an interdisciplinary CPRP approach for patients diagnosed with headache can be effective in helping to decrease pain, as well as normalize mood and function. Thus, CPRPs serve as an alternative treatment to multidisciplinary headache programs, interventional pain techniques, and primary care standard headache care.